Islamic Social Security - Syufaat, Syufaat (International Conference of Moslem Society, 2019)
Public welfare is one of the ideals that Islam wishes in order to realize the physical and spiritual prosperity. Efforts to realize it is to bring social welfare into reality through the principles of solidarity to achieve a sense of security for all human life, by which then it is known as the social security system (SSS). One of the issues of today’s urban society is the availability of social security to meet basic human needs which covers the needs of food, clothing, housing, education, health, energy sources, sanitation, transportation and information. Islamic social security is not limited merely to meet the materialistic and hedonistic basic needs, but it meets spiritual needs that are more essential.